2022
DOI: 10.1177/01945998221076998
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Analysis of the Facial Recess: Impact on Posterior Tympanotomy Difficulty During Pediatric Cochlear Implantation

Abstract: Objectives We analyzed several radiological features of the facial recess to correlate them with the intraoperative findings to highlight the most reliable predictors of posterior tympanotomy difficulty. Study Design Retrospective observational cohort study. Setting Multicenter study at tertiary referral institutions. Methods We included 184 pediatric patients who underwent cochlear implantation through the posterior tympanotomy approach. The correlation was attempted between 8 radiological features in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although both the anterior and lateral displacement of the VPFN may affect the RW accessibility, Elzayat et al found that the PT difficulty was statistically related more to the lateral displacement of the VPFN in their radiological analysis of the FR and evaluating its impact on the CI surgery. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Although both the anterior and lateral displacement of the VPFN may affect the RW accessibility, Elzayat et al found that the PT difficulty was statistically related more to the lateral displacement of the VPFN in their radiological analysis of the FR and evaluating its impact on the CI surgery. 14 …”
Section: Discussionmentioning
confidence: 99%